FUN VOCABULARY LEARNING IN EFL CLASSROOM THROUGH CHARADES GAME: WHY NOT? - Nur Halimah; Megawati Basri (Universitas Ahmad Dahlan)
The purposes of this paper are to portray charades game in learning vocabulary mastery in EFL classroom and tell the readers that this game is effective in every skill. This game has the activities like teamwork, served some topic given by the teacher, then she list the mistakes, then the last is reviewing by the teacher. The game enables the students to acquire new experiences in foreign language then fun and enjoyable environment is able to raise students’ motivation in learning. Vocabulary mastery is one of the most effective skills which may improve the students’ achievement in learning a language in the classroom. The students who have great quantities of vocabularies will bring them to be a great in mastering four crucial skills in English. They could easily do their task in the process of learning without any panicky or something disturbs their mind about the word. Meanwhile, English as a foreign language in Indonesia is still hard to get to serve for Indonesian students especially. Some of them have not remember well yet single word or vocabulary even though they have learned for almost twelve years if we count from primary school till college.